2014
DOI: 10.1073/pnas.1324115111
|View full text |Cite
|
Sign up to set email alerts
|

Marine ammonia-oxidizing archaeal isolates display obligate mixotrophy and wide ecotypic variation

Abstract: Ammonia-oxidizing archaea (AOA) are now implicated in exerting significant control over the form and availability of reactive nitrogen species in marine environments. Detailed studies of specific metabolic traits and physicochemical factors controlling their activities and distribution have not been well constrained in part due to the scarcity of isolated AOA strains. Here, we report the isolation of two new coastal marine AOA, strains PS0 and HCA1. Comparison of the new strains to Nitrosopumilus maritimus str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
344
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 310 publications
(374 citation statements)
references
References 60 publications
28
344
2
Order By: Relevance
“…N. brevis genome vs. 31 in N. maritimus) and holds even when these estimates are normalized to genome size (14.6 vs. 18.9 ABC transporters per millions of base pairs genome). The identification and expression of two Amt-type ammonium transporters (T478_1378, T478_1350) gives further support for the hypothesis that ammonia-oxidizing archaea actively transport ammonium (NH 4 + ) into the cell (13,20) and is consistent with detection of these genes in environmental metatranscriptomes (8,57).…”
Section: Comparative Genomic Analyses Suggest Adaptations To the Surfacesupporting
confidence: 64%
See 3 more Smart Citations
“…N. brevis genome vs. 31 in N. maritimus) and holds even when these estimates are normalized to genome size (14.6 vs. 18.9 ABC transporters per millions of base pairs genome). The identification and expression of two Amt-type ammonium transporters (T478_1378, T478_1350) gives further support for the hypothesis that ammonia-oxidizing archaea actively transport ammonium (NH 4 + ) into the cell (13,20) and is consistent with detection of these genes in environmental metatranscriptomes (8,57).…”
Section: Comparative Genomic Analyses Suggest Adaptations To the Surfacesupporting
confidence: 64%
“…For example, putative transport proteins for the import of lipoproteins, glycerol, and glycine betaine were all identified in the genome, with several present in the proteome, suggestive of potential alternative substrate use. Similarly, the persistence of a small percentage (<10% of total cells) of putatively heterotrophic bacterial cells in the enrichment culture and reports of reliance on organic compounds in other marine Thaumarchaeota (13) leave open the potential that Ca. N. brevis may benefit from organic compounds produced by the bacteria or in the natural seawater medium for growth.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Microbes, including the documented emergence of archaeal strains in 2007, have been shown to be integral decomposers of residual inputs and biosolids in corn agroecosystems [70][71][72]. In this process, these archaeal strains are also known to be potent contributors to soil N 2 O emissions and may be able to contribute even amid the presence of any nitrification inhibition [73], indicating a widespread genomic adaptability distinct from AOB populations, [74][75][76]. It has also been suggested that N 2 O is emitted as a spontaneous metabolic AO intermediate [73].…”
Section: Discussionmentioning
confidence: 99%